Perencanaan penjadwalan preventif maintenance mesin cold press pada PT. XYZ - Ismail; Marwan; Catur Yudhistira , Oza (LPPM-ITEBA, 2024)
The development of the manufacturing industry is currently experiencing rapid progress in line with the development of the global manufacturing industry. In line with this, it certainly has an impact on producers or suppliers. Companies are required to always provide satisfaction to consumers or customers, namely by providing services and providing products of the highest quality. Good products are of course produced through the best process as well. Increasing productivity in the production system is an absolute thing that must be done. To achieve production productivity, namely by increasing or rehabilitating production machines at the company. In producing a product, maintenance activities are needed. Maintenance is an activity to maintain the reliability of a facility so that the facility can function properly and is ready to function. Regular maintenance is expected to extend the life of production machines so they don't get damaged and don't interfere with production activities.